Pengaruh pola makan, faktor ekonomi, dan hemoglobin terhadap kebugaran fisik pada remaja - Sari, Dira Kurnia; Welis, Wilda; Rifki, Muhammad Sazeli; Effendi, Hastria; Hendra, Jhony (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
Increased understanding of a balanced diet, the role of economic factors, and the importance of hemoglobin levels are essential for improving students' physical fitness. This research aims to determine the influence of food patterns, economic factors, and hemoglobin on students' physical fitness. The research method uses quantitative survey methods and path analysis. The sample involved 58 adolescent students selected through simple random sampling. Data collection included a closed questionnaire on diet and economic factors, BMI measurements based on age and gender norms, physical fitness tests using the Nusantara Student Fitness Test, and hemoglobin level assessments according to WHO standards. The data analysis employed normality and homogeneity tests, with t-tests to determine variable effects using SPSS 25. The results concluded that dietary patterns and economic factors significantly influence hemoglobin, with p-values of 0.041 and 0.028. The R Square value of 0.427 indicates that these factors explain 42.7% of hemoglobin variability. The variables of diet, economic factors, and hemoglobin were significant to physical fitness, with p-values of 0.044, 0.000, and 0.006, respectively. The R Square value of 0.724 indicates that these three variables can explain 72.4% of the variability in physical fitness. This study contributes to demonstrating the impacts of diet, economic factors, and hemoglobin on students' physical fitness. Path analysis clarifies the relationships between these variables, while comprehensive fitness assessments provide insights into hemoglobin's impact on performance.